Story to Change Culture on Early Childhood in Australia - Nathaniel Kendall-Taylor; Annette Michaux; Donna Cross; Karen Forde (MDPI AG, 2023)
The goal of the article is to support the early childhood sector's efforts to increase the salience of early childhood as a social issue and change policy and practice to better support young children and their families. Cultural models shape how people think about social issues and support solutions. Changing how issues are framed-how they are presented, positioned and focused-can help shift these models and facilitate culture change. Using mixed methods research, we identified cultural models that members of the Australian public use to think about early childhood and compared these mindsets to concepts that the sector seeks to advance. This revealed a set of gaps in understanding that make it difficult for the sector to advance its agenda. We then designed and tested framing strategies to address these challenges and improve the salience of early childhood as a social issue, increase understanding of key concepts and build support for policies, programs and interventions. Findings point to strategies that advocates, service providers and funders can use to communicate more effectively about the importance of the early years.